Ongoing clinical trials and treatment options for patients with systemic sclerosis–associated interstitial lung disease. (8th June 2018) - Khanna, Dinesh; Tashkin, Donald P; Denton, Christopher P; Lubell, Martin W; Vazquez-Mateo, Cristina; Wax, Stephen
Abstract: SSc is a rare CTD that affects multiple organ systems, resulting in substantial morbidity and mortality. Evidence of interstitial lung disease (ILD) is seen in ∼80% of patients with SSc. Currently there is no approved disease-modifying treatment for ILD and few effective treatment options are available. CYC is included in treatment guidelines, but it has limited efficacy and is associated with toxicity. MMF is becoming the most commonly used medication in clinical practice in North America and the UK, but its use is not universal. Newer agents targeting the pathogenic mechanisms underlying SSc-ILD, including fibrotic and inflammatory pathways, lymphocytes, cell–cell and cell–extracellular membrane interactions, hold promise for better treatment outcomes, including improved lung function, patient-related outcomes and quality of life. Here we review ongoing trials of established and novel agents that are currently recruiting patients with SSc-ILD.